UNJUK KERJA DAN PEMANFAATAN INVERTER SEBAGAI PENGENDALI KECEPATAN MOTOR INDUKSI 3 PHASA - Anton anton; Tuti Angraini (Teknik Elektro Politeknik Negeri Padang, 2013)
The Induction motors are found in industrial and domestic environments because of low cost of operation including, induction motors are widely used induction motor 1 phase and 3 phase. During operation of induction motors generally used at normal speed, but the specific purpose induction motors operated with variable speed. In order to obtain varying motor speed can be controlled using the inverter. The use of inverters here to give supplay voltage AC induction motor in which the magnitude of the frequency can be varied. Setting frequency of the inverter utilizing method pulse with modulation (PWM). The circuit used to build PWM, using Insulated Gate Bipolar Transistor (IGBT) technology. Values ​​obtained variable frequency ranging from 4 Hz to 50 Hz, and acquired motor speed ranging from 12 rpm up to 1390 rpm.